Media Exposure of the Farmers in Sagar District of Madhya Pradesh - Singh, D.K.; Gautam, U.S.; Singh, Mukesh; Singh, R.P. (Indian Journal of Extension Education, 2010)
The extension contact and Mass Media play an important role in transmitting viable information to users through various sources and channels for the diffusion of the new technology in order to bring about awareness and changes in the attitudes of farmers. The study was conducted in Sagar district of Madhya Pradesh. Four development blocks were selected randomly in two villages from each selected block with the help of random sampling technique and from each village 30 cultivators were selected randomly. Hence, the total number of selected respondents were 240 spread over eight villages. The findings of the study clearly show that the RAEO’s are the most effective and sought after interpersonal media of the farmers, the reason being that the RAEO’s are easily within the approach of the farmers. Similarly, the popular mass media, like newspapers, radio and television are the most sought after channel by the farmers. Hence, extensive use of these channels should be made to reach the farmers.